Faktor-Faktor Yang Berhubungan Dengan Keluhan Low Back Pain Pada Pekerja Pt. D P S - Ridhorafiardi Pratama; Eti Kurniawati; Ahmad Husaini (Awatara Publisher, 2026)
Low back pain (LBP) remains one of the most common occupational health problems among palm oil workers due to non-ergonomic work postures, excessive muscle strain, and repetitive activities. This study aimed to determine the factors associated with low back pain complaints among workers at PT. Damasaraya Palma Sejahtera, Jambi Province, in 2024. This study used a quantitative analytic design with a cross-sectional approach. The population consisted of 45 loading and unloading workers, and the sampling technique used total sampling. Data collection was carried out using questionnaires, observation sheets, and ergonomic assessment methods. Data were analyzed using univariate and bivariate analyses with the chi-square test. The results showed that there was a significant relationship between working period and low back pain complaints (p=0.014), physical workload and low back pain complaints (p=0.000), work posture and low back pain complaints (p=0.022), and repetitive movements and low back pain complaints (p=0.007). Workers who had long working periods, heavy workloads, non-ergonomic postures, and repetitive movements had higher risks of experiencing low back pain complaints. The study concludes that occupational ergonomic factors significantly contribute to low back pain among palm oil loading workers. Therefore, companies are expected to implement ergonomic interventions, provide occupational safety training, and improve work methodsto reduce musculoskeletal complaints among workers.